2014
DOI: 10.1108/scm-06-2013-0191
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation processes – antecedents for building supply chain resilience

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
394
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(414 citation statements)
references
References 62 publications
(123 reference statements)
6
394
0
14
Order By: Relevance
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
See 2 more Smart Citations
“…Natural disaster Jahre & Heigh, 2008;McLachlin et al 2009;Charles, 2010;Gatignon et al 2010;Jahre & Jensen, 2010;Oloruntoba, 2010;Duran et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Buddas, 2014;Ergun et al 2014;Scholten et al 2014;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;War/terrorism Listou, 2008McLachlin et al 2009;Choi et al 2010;Jahre & Jensen, 2010;McCoy et al 2011;Pedraza Martinez et al 2011;Cozzolino et al 2012;Pedraza Martinez & Van Wassenhove, 2013;Besiou et al 2014;Buddas, 2014;Eftekhar et al 2014;Gralla et al 2015;Kunz et al 2015 Jahre & Heigh, 2008;Listou, 2008;Charles, 2010;Gatignon et al 2010;Duran et al 2011 ;Pedraza Martinez et al 2011;Besiou et al 2014;Buddas, 2014;Gralla et al 2015;Gralla et al 2015;Jahre & Fabbe-Costes, 2015;Stauffer et al 2015;Jahre et al 2016 Manufacturing risk factors Supply ris...…”
Section: Type Of Risk Reference Abnormalunclassified
“…Iakovou et al (2014) suggested dual sourcing as a proactive risk mitigation sourcing strategy. Scholten et al (2014) showed the importance of collaboration, supply chain re-engineering, agility, risk awareness, and knowledge management. Kóvacs and Tatham (2009) discussed the use of vendor-managed inventory, public-private partnerships, joint warehouses for resource pooling, and postponement.…”
Section: "Where Is the Crisis Management Component Of [Humanitarian Omentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns autores (PETTIT; FIKSEL; CROXTON, 2010;SCHOLTEN;SCOTT;FYNES, 2014;JOHNSON;ELLIOTT;DRAKE, 2013;SHEFFI;RICE, 2005) consideram pontos distintos para cada facilitador e esta riqueza de detalhamento será evidenciada na discussão apresentada nesta seção. O Quadro 4 apresenta os facilitadores, bem como uma breve definição de cada um deles e as principais referências utilizadas para a construção da definição.…”
Section: Facilitadores à Resiliência Na Cadeia De Suprimentosunclassified
“…La recuperación incluye las acciones ejecutadas en el largo plazo que permiten a la comunidad estabilizarse y retornar a su situación de normalidad (Altay & Green, 2006). El proceso de la logística humanitaria presenta un comportamiento cíclico, ya que las situaciones vividas en la respuesta al desastre y las lecciones aprendidas en la fase de recuperación, pueden verse reflejadas en obras de reconstrucción y nue-Juan Camilo López-Vargas Diana María Cárdenas-Aguirre vos planes de mitigación que reduzcan los riesgos de nuevos desastres (Baldini, et al, 2012;Hadiguna, et al, 2014;Scholten, et al, 2014;Hoyos, et al, 2015).…”
Section: Introductionunclassified